Molecular and Toxicity Analyses of White Granulated Sugar and Other Processing Products Derived From Transgenic Sugarcane - Wang, Wenzhi; Yang, Benpeng; Wang, Juangang; Feng, Xiaoyan; Feng, Cuilian; Zhao, Tingting; Shen, Linbo; Wang, Qinnan; Wu, Zhuandi; Zhang, Shuzhen; Ma, Zhengqiang (Frontiers in Plant Science, 2020)
This study aimed to prepare the sugar industry for the possible introduction of genetically modified (GM) sugarcane and derived retail sugar products and to address several potential public concerns regarding the characteristics and safety of these products. GM sugarcane lines with integrated Cry1Ab and EPSPS foreign genes were used for GM sugar production. Traditional Polymerase Chain Reaction (PCR), real-time fluorescent quantitative PCR (RT-qPCR), and enzyme-linked immunosorbent assay (ELISA) were performed in analyzing leaves, stems, and other derived materials during sugar production, such as fibers, clarified juices, filter mud, syrups, molasses, and final GM sugar product . The toxicity of GM sugar was examined with a feeding bioassay using Helicoverpa armigera larvae. PCR and RT-qPCR results showed that the leaves, stems, fibers, juices, syrups, filter mud, molasses, and white granulated sugar from GM sugarcane can be distinguished from those derived from non-GM sugarcane. The RT-qPCR detection method using short amplified product primers was more accurate than the traditional PCR method. Molecular analysis results indicated that trace amounts of DNA residues remain in GM sugar, and thus it can be accurately characterized using molecular analysis methods. ELISA results showed that only the leaves, stems, fibers, and juices sampled from the GM sugarcane differed from those derived from the non-GM sugarcane, indicating that filter mud, syrup, molasses, and white sugar did not contain detectable Cry1Ab and EPSPS proteins. Toxicity analysis showed that the GM sugar was not toxic to the Helicoverpa armigera larvae. The final results showed that the GM sugar had no active proteins despite containing trace amounts of DNA residues. This finding will help pave the way for the commercialization of GM sugarcane and production of GM sugar.